Efficacy of Ovixcell Extender for Cryopreservation of Buck Epididymal Spermatozoa - Sakeena, Sadaf; Naikoo, Mehrajuddin; Khatun, Arjuma; Sofi, Khursheed A; Andrabi, Mudasir A; Ahmad, Tavsief; Pampori, Zahoor Ahmad (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Cryopreservation of spermatozoa is a cornerstone of reproductive biotechnology, enabling long-term storage of genetic material from  livestock and endangered species. However, the freezing-thawing process predisposes spermatozoa to cryoinjuries, including osmotic  stress, oxidative damage, and alterations in membrane integrity. This study evaluated the efficacy of Ovixcell, a soy lecithin-based  extender, in preserving buck epididymal spermatozoa during cryopreservation. Testes (n=40) were collected from freshly slaughtered  bucks, and spermatozoa were retrieved from the cauda epididymides. Samples with >70% motility were cryopreserved using Ovixcell  supplemented with 7% glycerol. Sperm quality was assessed pre-freeze and post-thaw using standard procedures, including motility,  CFDA and PI dual staining for viability, hypo-osmotic swelling test (HOST) and acrosomal integrity using Giemsa staining. The results  showed a significant (p < 0.0001) reduction in sperm characteristics from pre-freeze to post-thaw stage. The motility decreased from  82.60% to 63.80%, viability from 80.47% to 61.13%, plasma membrane integrity from 92.16% to 59.40%, and acrosomal integrity from  90.92% to 63.43%. Despite this decline, post-thaw values remained within the acceptable range for further use. The findings confirm  that Ovixcell stabilizes sperm membranes effectively and serves as a good sperm extender, supporting artificial insemination and  conservation programmes through retrieval and storage of epididymal spermatozoa.
Keywords: Buck, Cryopreservation, Ovixcell, Post-thaw, Sperm quality parameters